Study of Cardiorespiratory Endurance and Muscle Strength in Volleyball Players in The Training to Win Phase - Viva Lenia Davina Permata; Arief Darmawan (Journal of Physical and Outdoor Education, 2025)
Physical fitness is essential in volleyball as it directly contributes to an athlete’s performance, especially during the training to win phase which demands peak competitive condition. This study aims to assess the physical fitness quality of volleyball athletes in Malang City as a basis for evaluating training programs. The study employed a descriptive quantitative survey design involving 33 selected athletes (13 males and 20 females). The physical fitness tests included push-ups, sit-ups, vertical jumps, and the beep test. Results showed the average scores were 31.25 for push-ups (SD = 11.37), 47.2 for sit-ups (SD = 6.13), 14.54 cm for vertical jumps (SD = 5.74), and 36.02 for the beep test (SD = 5.87). These findings indicate that the athletes' overall physical fitness falls within a moderate category, with noticeable performance gaps, particularly in upper-body strength and cardiovascular endurance. The results highlight the need for more targeted and structured physical conditioning programs. This study can serve as a reference for designing future training regimens and as a foundation for long-term physical development in volleyball athletes in Malang City.